Still Not There: The Continued Invisibility of Female Athletes and Sports in the New Zealand Print Media. Issue 1 (August 2013) - French, Simone
This research examined parity for female athletes compared with male athletes in the level of coverage received in the New Zealand print media in a year that did not contain either the Commonwealth or Olympic Games. Using content analysis, 562 sport news articles from the New Zealand Herald and the Dominion Post were analysed. The findings revealed that female athletes received 6.1 per cent of coverage compared with male athletes, who received 73.6 per cent; articles related to female athletes/sports had an average length of 432 words compared with 461 words for articles related to male athletes/sports. These data are a stark illustration that, even in a country where women led the world in achieving suffrage, continuing cultural change is not guaranteed.